Comparative evaluation of the symmetric and asymmetric Marcus-Hush formalisms of electrode kinetics - The one-electron oxidation of tetraphenylethylene in dichloromethane on platinum microdisk electrodes - Suwatchara, D; Henstridge, M; Rees, N; Laborda, E; Compton, R (2012)
We report an experimental comparative evaluation of the Butler-Volmer (BV), symmetric and asymmetric Marcus-Hush (MH) kinetic formalisms. Numerical simulations using these kinetic models are employed to fit experimental cyclic voltammetry of the one-electron oxidation of tetraphenylethylene in dichloromethane under conditions of full electrolyte support at a platinum microdisk electrode. When compared with the BV formalism, the symmetric MH model is seen to give rise to an inferior quality of fit determined by calculating the mean scaled absolute deviation (MSAD) between theory and experiment. This can be traced to its inherent assumption of identical force constants of the reagent and product, rendering it unable to address the asymmetry that exists between the forward and reverse sweeps of the cyclic voltammetry due to the difference in force constants. Where the asymmetric MH formalism is used, cyclic voltammograms with comparable quality of fit to that of BV are obtained. The best-fit parameters obtained for each kinetic model (25 °C) are: Butler Volmer: k 0 = 0.17 cm s -1, α = 0.65 Symmetric Marcus-Hush: k 0 = 0.15 cm s -1, λ ≥ 0.53 eV Asymmetric Marcus-Hush: k 0 = 0.15 cm s -1, λ ≥ 0.53 eV, β/λ = 0.55 eV -1. © 2012 Elsevier B.V. All rights reserved.